The Influence Of Profitability, Liquidity, Leverage, And Dividend Policy On Investor Response: Firm Size As A Moderation - Anggita Ika Lilyani; Akhmad Riduwan; Bambang Suryono (Lead Journal of Economy and Administration, 2023)
This study aimed to examine the effect of profitability, liquidity, leverage, and dividend policy on investors’ response; with firm size as the moderating variable. Moreover, the study was quantitative. The data collection technique used purposive sampling. In line with that, there were 334 samples from 39 Property and Real Estate companies listed on the Indonesia Stock Exchange during 2012-2021. Furthermore, the data analysis technique used multiple linear regression. As the result concluded that (a) profitability had a positive effect on investors’ response;(b) liquidity had a positive effect on investors’ response; (c) leverage did not affect investors’ response; (d) dividend policy did not affect investors’ response; (e) firm size was not able to moderate the effect of profitability on investors’ response; (f) firm size was able to moderate positively the effect of liquidity on investors’ response; (g) firm size was not able to moderate the effect of leverage on investors’ response; and (h) firm size was not able to moderate the effect of dividend policy on investors’ response.